The Effect Of Independent Commissioner Proportion, Green Investment, And Leverage On Carbon Emission Disclosure - Maharani, Putri Dewi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study analyzes the effect of independent commissioner proportion, green investment, and leverage on carbon emission disclosure. The sample consists of 15 companies in the transportation, logistics, and automotive subsectors listed on the Indonesia Stock Exchange, observed from 2021 to 2023, yielding 45 purposively selected data points. Multiple linear regression analysis was conducted using SPSS Statistics 25 to test the hypotheses. The results indicate that both independent commissioner proportion and green investment have a positive effect on carbon emission disclosure, while leverage shows no significant effect. These findings highlight the role of robust corporate governance and environmental investment in enhancing corporate accountability on carbon-related practices.